2021
DOI: 10.1136/bmjopen-2020-047067
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Prevention Education Program in a population with pre-diabetes in Nepal: a study protocol of a cluster randomised controlled trial (DiPEP)

Abstract: IntroductionEvidence suggests that diabetes burden can be reduced by implementing early lifestyle intervention programmes in population with pre-diabetes in high-income countries. However, little is known in developing nations like Nepal. This study aims to assess effectiveness of community-based Diabetes Prevention Education Program (DiPEP) on haemoglobin A1c (HbA1c) level, proportion of pre-diabetes reverting to normoglycaemia, diet, physical activity, weight reduction, diabetes knowledge and health literacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…The present study is a community-based cross-sectional study from the DiPEP project which included screening campaigns to detect prediabetes in the community and a cluster randomised controlled trial (RCT). 27 The study was conducted in two urban settings in Nepal, Patan and Dhulikhel, from October 2019 to March 2020. Community screening campaigns were conducted in 10 clusters of Patan and 2 clusters of Dhulikhel.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study is a community-based cross-sectional study from the DiPEP project which included screening campaigns to detect prediabetes in the community and a cluster randomised controlled trial (RCT). 27 The study was conducted in two urban settings in Nepal, Patan and Dhulikhel, from October 2019 to March 2020. Community screening campaigns were conducted in 10 clusters of Patan and 2 clusters of Dhulikhel.…”
Section: Methodsmentioning
confidence: 99%
“…Two originally proposed clusters from Dhulikhel were excluded due to the COVID-19 pandemic. 27 Hence, there were a total of 12 clusters in the study representing urban settlements with similar healthcare services. Permanent residents of the study sites aged 18–64 years with no self-reported history of diabetes were eligible for the screening.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To the researchers’ knowledge, no studies in Nepal have yet explored or reported experiences of people with prediabetes who underwent diabetes prevention intervention programs at the community level; such experiences can be helpful to reach people better and/or improve certain aspects of the interventions. Recently, a community-based cluster randomized controlled trial (RCT) investigating the effect of an intervention called “Diabetes Prevention Education Program (DiPEP)” was conducted in Nepal [ 36 ]. It was a group-based lifestyle intervention program designed with inspiration from the National Diabetes Education Program [ 37 ] and the DPP [ 22 ] from the USA.…”
Section: Introductionmentioning
confidence: 99%